2016
DOI: 10.1038/srep23191
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of diaminopimelic acid biosynthesis allows characterisation of Mycobacterium tuberculosis N-succinyl-L,L-diaminopimelic acid desuccinylase

Abstract: With the increased incidence of tuberculosis (TB) caused by Mycobacterium tuberculosis there is an urgent need for new and better anti-tubercular drugs. N-succinyl-L,L-diaminopimelic acid desuccinylase (DapE) is a key enzyme in the succinylase pathway for the biosynthesis of meso-diaminopimelic acid (meso-DAP) and L-lysine. DapE is a zinc containing metallohydrolase which hydrolyses N-succinyl L,L diaminopimelic acid (L,L-NSDAP) to L,L-diaminopimelic acid (L,L-DAP) and succinate. M. tuberculosis DapE (MtDapE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…These mutants were significantly underrepresented by up to 8-fold upon RIF treatment specifically in cholesterol growth conditions across multiple sspB doses and drug concentrations. To further explore the effect of cell wall inhibition, we tested individual mutants with defects in peptidoglycan ( dapE ), arabinogalactan ( aftB ), and mycolic acid ( hadB ) synthesis (45, 4749). In this format, we found that perturbation in each of these cell wall layers produced a similar effect, as they all preferentially sensitized the bacterium to RIF in cholesterol growth conditions (Fig4BCD) .…”
Section: Resultsmentioning
confidence: 99%
“…These mutants were significantly underrepresented by up to 8-fold upon RIF treatment specifically in cholesterol growth conditions across multiple sspB doses and drug concentrations. To further explore the effect of cell wall inhibition, we tested individual mutants with defects in peptidoglycan ( dapE ), arabinogalactan ( aftB ), and mycolic acid ( hadB ) synthesis (45, 4749). In this format, we found that perturbation in each of these cell wall layers produced a similar effect, as they all preferentially sensitized the bacterium to RIF in cholesterol growth conditions (Fig4BCD) .…”
Section: Resultsmentioning
confidence: 99%
“…Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) (Perkin-Elmer Optima 5300 DV, Model S10) was used to determine the S, Zn, Cd, and Cu contents of the purified proteins as described previously [ 73 , 74 ]. In addition, the protein concentration was also routinely determined from the concentration of free thiols (cysteine) in the EDTA-demetallated proteins by Ellman’s reagent, 5,5′-dithio-bis(2-nitrobenzoic acid) (DTNB) at 412 nm by UV–visible spectroscopy using N -acetyl-cysteine as standard (Biomate 3 spectrophotometer, Fisher Scientific, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Mycobacterium tuberculosis DapE was found to be insensitive to the known DapE inhibitor L-captopril (Usha et al . 2016). Finally, DapF in Chlamydia trachomatis is bifunctional and involved in both mDAP synthesis and the racemisation of glutamate (Liechti et al .…”
Section: Introductionmentioning
confidence: 99%